Engineering a semi-interpenetrating constructed xylan-based hydrogel with superior compressive strength, resilience, and creep recovery abilities. (15th October 2022) - Han, Tingting; Song, Tao; Pranovich, Andrey; Rojas, Orlando J.
Abstract: Recent advances in the area of hydrogel synthesis have been directed to enhance the mechanical properties and biocompatibility, which are critical in their use as functional biomaterials. In this work, a green and facile method is introduced to produce a hydrogel based on xylan, a plant-based heteropolysaccharide, that is shown to successfully form hydrogen-bonded, semi-interpenetrating polymer networks with polyvinyl alcohol. Upon crosslinking with sodium trimetaphosphate, the obtained hydrogels achieved an exceptional compressive strength (up to 84.2 MPa at a fracture strain of 90 %), which surpasses any polysaccharide-based hydrogels reported so far. The hydrogels were further shown to have high degradation temperature (350–370 °C), to be mechanically resilient with a form and creep recovery of 95 % (78 % stress after 1000 cycles under 30 % strain) and 98 % in height, respectively. All materials used in the preparation of the hydrogels were non-toxic and biocompatible, which makes the synthesized hydrogels suitable potential candidates for soft-tissue engineering and biomedical applications. Graphical abstract: The successful construction of semi-interpenetrating network enhanced xylan-based hydrogel with superior compressive strength, resilience and creep recovery abilities. Unlabelled Image